Allatotropin: A pleiotropic neuropeptide that elicits mosquito immune responses - Hernández Martínez, Salvador (2017)
Allatotropins (AT) are neuropeptides with pleotropic functions on a variety of insect tissues. They affect processes such as juvenile hormone biosynthesis, cardiac rhythm, oviduct and hindgut contractions, nutrient absorption and circadian cycle. The present work provides experimental evidence that AT elicits immune responses in two important mosquito disease vectors, Anopheles albimanus and Aedes aegypti. Hemocytes and an immune-competent mosquito cell line responded to AT by showing strong morphological changes and increasing bacterial phagocytic activity. Phenoloxidase activity in hemolymph was also increased in Ae. aegypti mosquitoes treated with AT but not in An. albimanus, suggesting differences in the AT-dependent immune activation in the two species. In addition, two important insect immune markers, nitric oxide levels and expression of antimicrobial peptide genes, were increased in An. albimanus guts after AT treatment. AT conjugated to quantum dot nanocrystals (QDots) specifically labeled hemocytes in vivo in both mosquito species, implying molecular interactions between AT and hemocytes. The results of our studies suggest a new role for AT in the modulation of the immune response in mosquitoes.